2017
DOI: 10.1152/ajpendo.00111.2016
|View full text |Cite
|
Sign up to set email alerts
|

Central effects of insulin detemir on feeding, body weight, and metabolism in rats

Abstract: Insulin detemir (DET) is a basal insulin analog that, in contrast to other long-acting forms of insulin, has significant weight-gain-sparing effects in diabetic patients. We hypothesized that this effect of DET may be due to its enhanced catabolic action in the central nervous system. We investigated the long-term effects of single third ventricular (3V) microinjections of equimolar doses of DET and regular insulin in normal male rats on feeding, body weight, energy expenditure (EE), and respiratory quotient (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…42,43 The effect of central insulin administration on body weight is in contrast to peripheral administration of insulin, which has anabolic effects. 44 The central anorectic effects of insulin have subsequently been replicated in rats [45][46][47][48] and mice. [49][50][51] Acute administration of insulin into the brain decreases food intake dose-dependently 48,52 and reduces body weight for a period of approximately 24-48 hours following infusion, 29,47 whereas chronic administration of cerebral insulin reduces both food intake and body weight over a longer time period.…”
Section: In Sulin ' S Role In Food Intakementioning
confidence: 99%
See 2 more Smart Citations
“…42,43 The effect of central insulin administration on body weight is in contrast to peripheral administration of insulin, which has anabolic effects. 44 The central anorectic effects of insulin have subsequently been replicated in rats [45][46][47][48] and mice. [49][50][51] Acute administration of insulin into the brain decreases food intake dose-dependently 48,52 and reduces body weight for a period of approximately 24-48 hours following infusion, 29,47 whereas chronic administration of cerebral insulin reduces both food intake and body weight over a longer time period.…”
Section: In Sulin ' S Role In Food Intakementioning
confidence: 99%
“…44 The central anorectic effects of insulin have subsequently been replicated in rats [45][46][47][48] and mice. [49][50][51] Acute administration of insulin into the brain decreases food intake dose-dependently 48,52 and reduces body weight for a period of approximately 24-48 hours following infusion, 29,47 whereas chronic administration of cerebral insulin reduces both food intake and body weight over a longer time period. 36,53,54 Rodent studies examining the metabolic and behavioural effects of intracranial insulin infusion usually employ i.c.v.…”
Section: In Sulin ' S Role In Food Intakementioning
confidence: 99%
See 1 more Smart Citation
“…In this same report, ArcN Ex-4 reliably suppressed the increase in RER found after co-infusion of ghrelin and NPY (Abtahi et al, 2016). As a result, and in order to further investigate the metabolic function of hypothalamic GLP-1, ghrelin, and NPY, in the present study we targeted the PVN, given the well-established role of th is nucleus in regulating energy metabolism and substrate oxidation (Currie et al, 2010; Gao et al, 2018; Thomas et al, 2015; Vasselli et al, 2017). Specifically, the overall objective of the current report was to initially compare the impact of acyl and des-acyl ghrelin on energy substrate utilization.…”
Section: Introductionmentioning
confidence: 99%
“…This finding is in contradistinction to the findings in rats, where whole body energy expenditure is significantly increased with insulin detemir after 72 hours as compared with regular human insulin. 22 In the same study, there was reduced food intake in insulin detemir group compared to regular human insulin. 22 Previous studies have shown an effect of insulin detemir to reduce food intake as compared to NPH insulin, but NPH is also known to cause more frequent hypoglycemia compared to insulin glargine or detemir.…”
Section: Discussionmentioning
confidence: 84%